CANCEL CULTURE SEBAGAI RESPONS MASYARAKAT TERHADAP PELAKU KASUS PERSELINGKUHAN : KAJIAN PADA AKUN INSTAGRAM @ARAWINDAK - Jehovani Ratna Mourina, Stella; Lukmantoro, Triyono; Naryoso, Agus (Interaksi Online, 2024)
The cancel culture phenomenon emerges as a form of public rejection of public figures who behave deviantly. The research aims to understand the cancel culture phenomenon and various related actions by examining the cancel culture phenomenon that occurred to an actress involved in an affair, Arawinda Kirana. Arawinda Kirana is a newcomer actress whose name began to be recognized by the public through the movie Yuni (2021). In the film Arawinda Kirana plays the role of Yuni, through which Arawinda Kirana received awards, one of which was the winner of the 2021 Citra Cup in the category of Most Favorite Female Lead Actress, she is also known for creating the hashtag #BerkainBersama, a movement that invites young people to preserve and use kebaya, and she is familiarly known to the public as "Kartini Modern" From the data, it was found that Arawinda Kirana experienced a change in response from the public. Before cancel culture Arawinda was known as a talented young actress and was also known as a modern kartini' who received a lot of public support, praise both for her and her work. Changes in audience response after Arawinda Kirana experienced cancel culture are observed in the findings which are divided into the following categories: The increase in account performance and followers in the early days of cancel culture, comments that indicate stopping providing support to the target, comments that lead to calling out actions in comments containing suggestions and criticisms in comments which are divided into three types of calling out forms, namely the legal literacy group, defending justice for victims of infidelity and the group that criticizes moral and religious demands, no comments were found that vocally stated that they stopped supporting products or brands that were bound to collaborate with the target but in collaboration uploads, audience attention to the brand would be covered by the crowd of negative public comments directed at the target. Comments in the category of work rejection contain criticism of films that are not objective, insults to films, and invitations not to watch films, comments leading to virtual bullying contain swearing or sentences containing harsh words that are undirected and do not have clear definitions, insults that degrade the target's physique, forms of labeling comments to Arawinda Kirana such as "pelakor" "perek" "flirtatious" "home wrecker" "jablai" "gatal", and comments that degrade the target's physique